ANALISIS KINERJA KEUANGAN PEMERINTAH DESA BEJALEN KECAMATAN AMBARAWA, KABUPATEN SEMARANG TAHUN 2017-2018 - DESY DWI AYU LESTARI; INTAN BUNGA PERTIWI; MUHAMMAD MUCHLISUN; NUR KABIB; SAIFUL ANWAR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to examine how the financial performance of Bejalen Village Government, Ambarawa District, Semarang Regency, 2017-2018 Budget Year by analyzing the Budget Realization Report. The method used is descriptive qualitative using the effectiveness ratio and efficiency ratio. Data obtained through document studies and interviews. The data used in the form of data reports on the realization of the budget for the year 2017 to 2018. Based on the calculation of the ratio of effectiveness to efficiency of the ratio of the results of this study is the original village income budget with the realization of the original village income obtained from the second year 100% with the effective category. Raiso efficiency calculation that the average is 95.9% with an element of expenditure realization which has a less efficient budget category.